Bunuel wrote:
If \(x\) and \(y\) are integers, \(m = 3^{x-y}*5^{2y-1}*7^{4-x}\) and \(n = 105^y\), what is the value of \(y\)?
(1) \(n\) is NOT a multiple of \(m\).
(2) \(m\) is a multiple of \(n\).
Official Solution:If \(x\) and \(y\) are integers, \(m = 3^{x-y}*5^{2y-1}*7^{4-x}\) and \(n = 105^y\), what is the value of \(y\)? This is a highly challenging question that involves multiple mathematical concepts like number properties, exponents, divisibility, and inequalities. It's crucial to analyze all aspects thoroughly and systematically, breaking the problem into smaller parts and understanding the relationships between the variables.
(1) \(n\) is NOT a multiple of \(m\).
The above implies that \(\frac{n}{m} \neq {integer}\):
\(\frac{105^y}{3^{x-y}*5^{2y-1}*7^{4-x}} \neq {integer}\);
\(\frac{(3*5*7)^y}{3^{x-y}*5^{2y-1}*7^{4-x}} \neq {integer}\);
\(\frac{3^y*5^y*7^y}{3^{x-y}*5^{2y-1}*7^{4-x}} \neq {integer}\);
\(3^{y-(x-y)}*5^{y-(2y-1)}*7^{y-(4-x)} \neq {integer}\);
\(3^{2y-x}*5^{1-2y}*7^{x+y-4} \neq {integer}\).
The above expression is not an integer for different values of \(y\). For example, if \(x = y = 0\), \(3^{2y-x}*5^{1-2y}*7^{x+y-4}=3^0*5^1*7^{-4}=\frac{5}{7^4}\), which is not an integer. Alternatively, if \(x = 0\) and \(y = 1\), \(3^{2y-x}*5^{1-2y}*7^{x+y-4}=3^2*5^{-1}*7^{-3}=\frac{9}{5*7^3}\), which is not an integer either. Not sufficient.
(2) \(m\) is a multiple of \(n\).
The above implies that \(\frac{m}{n} = {integer}\):
\(\frac{3^{x-y}*5^{2y-1}*7^{4-x}}{105^y} ={integer}\);
\(\frac{3^{x-y}*5^{2y-1}*7^{4-x}}{(3*5*7)^y} = {integer}\);
\(\frac{3^{x-y}*5^{2y-1}*7^{4-x}}{3^y*5^y*7^y} = {integer}\);
\(3^{x-y-y}*5^{2y-1-y}*7^{4-x-y}= {integer}\);
\(3^{x-2y}*5^{y-1}*7^{4-x-y}= {integer}\).
Since \(x\) and \(y\) are integers, for the above expression to be an integer, all multiples must be integers and consequently all exponents must be non-negative. Therefore, several conditions must simultaneously be true:
\(x-2y \geq 0\).
\(y-1 \geq 0\).
\(4-x-y \geq 0\).
Adding the last two inequalities gives \(3-x \geq 0\). Adding this to the first inequality results in \(3-2y \geq 0\), which implies \(3 \geq 2y\). From the second inequality, we have \(2y-2 \geq 0\), or \(2y \geq 2\). Therefore, considering \(3 \geq 2y\) and \(2y \geq 2\), we get \(2 \leq 2y \leq 3\). Since \(y\) is an integer, \(y\) can only be 1. Sufficient.
Answer: B